Maintenance of oral hygiene of patients admitted to intensive care units in hospitals. - Silva Carlos Duarte , Antônio (Brazilian Journal of Implantology and Health Sciences, 2021)
Objective: The prevention of diseases and humanization of inpatients occurs with a greater integration of dentistry and medicine, aiming at a global treatment of patients. Therefore, this study aims to show the importance of the dentist, general practitioner, within an intensive care unit. Materials and methods: The methodology used was a questionnaire, in which some questions were asked to six doctors and six nurses responsible for the Intensive Care Units, of the four main hospitals in Passo Fundo / RS, seeking to evaluate the presence of the DC in the ICUs, the care performed, associated comorbidities and the degree of acceptance of dental professionals in these units. Result: The presence of a dental surgeon is not prioritized in two of the evaluated hospitals, in any of its three intensive care units, contrary to the legislation in force on April 18, 2013. Conclusion: It was concluded that it is of the utmost importance for the HC in the hospital network, aiming at an improvement in the clinical condition of inpatients, reduction of infections, reduction of medication and number of beds, attenuating the index of oral pathogens due to poor hygiene, reducing hospital costs and showing that it is necessary to insert the DC in the ICU multiprofessional team.